Primary Amenorrhea et Hematocolpos et Hematometra e.c Transverse Vaginal Spetum - Ahmad Hafid; Rodiani Rodiani; Marzuqi Sayuti (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2023)
Background: Amenorrhea is defined as the absence of menarche in females of reproductive age. Primary amenorrhea is the failure to reach menarche by age 13 with no secondary sexual characteristics if menarche has not occurred five years after initial breast development or if the patient is 15 years or older. A transverse vaginal septum is a rare congenital abnormality in Mullerian duct development that can cause primary amenorrhea. Transverse vaginal septum incidence ranges from 1:2.100 to 1:72.000. The surgical treatment should be carried out as early as possible to prevent vaginal stenosis. Objective: To describe a rare müllerian duct abnormality and its management. Methods: This study is a case report. Primary data was obtained through auto anamnesis, anamnesis, physical examination, and ultrasound workup. Result: A 15 years old girl complained of cyclical abdominal pain a year ago without a history of menstruation. Ultrasound examination showed signs of hematometra and hematocolpos. The septum location was approximately 3cm from the vaginal introitus. We performed simple excision of the septum, then the distal end of the vagina wall of the septum was sutured to the proximal end of the vaginal wall with a simple interrupted suture. The patient was then discharged in good condition. Conclusion: The transverse vaginal septum remains a rare anomaly of the female genital tract; the reasons for its discovery are highly variable according to its shape and location. Haematocolpos remains the main consequence of these septums. The management is based on surgery while considering the risks of postoperative stenosis and the repercussions on the upper genital tract